The Caribbean Community in transition : functional cooperation as a catalyst for change - Hall, Kenneth (Ian Randle Pub. KingstonJM, 2008)
Looks at functional cooperation as the mechanism to safeguard CARICOM's future. Presents functional cooperation as a catalyst for change and growth.